Bibliometric Analysis of the Role of Libraries in Achieving Sustainable Development Goals (SDGs) in International Scientific Publications 2015 – 2023 - Restiana Restiana; Retno Syekti (Budapest International Research and Critics University, 2023)
The role of libraries in supporting the achievement of Sustainable Development Goals (SDGs) has become increasingly important as awareness of sustainability and the importance of access to information grows. Bibliometric analysis of international scientific publications can provide an overview of the themes, contexts, and journals that most frequently publish articles related to the role of libraries in SDGs. Data collection was carried out using the Publish or Perish software and the Google Scholar database, and Boolean logic was used with the keywords